Mineral and Coal Mining Regulatory Reform in Indonesia - Rahman, Irsan; Widyawati, Anis; Suryani, Leony Sondang; Haris, Iyan Nurdiyan; Basrawi, Basrawi (Journal of Law and Legal Reform, 2025)
Mining in Indonesia is a vital sector that contributes significantly to the economy. However, current regulations still reveals a number of weaknesses that impact environmental sustainability and community welfare. These include weak law enforcement, lack of transparency and public participation at all stages of mining activities, inadequate mechanisms to ensure corporate social responsibility and environmental and post-mining reclamation, provisions that are not responsive to changing social and environmental conditions, further exacerbating the situation. This research uses a normative legal research method with an analytical approach to the provisions of laws and regulations based on facts obtained from secondary sources by paying attention to the credibility of these secondary sources. The main findings of the research reveal that environmental problems arise due to misalignment between mining laws and environmental laws. Environmental laws are not positioned as a command to mitigate the environmental impact of mining, and issues are further compounded by overlapping regulations on mining reclamation. The welfare of the community remains an unfulfilled promise, as environmental economic rights are increasingly eroded by the provisions in Article 162 of Law No. 3 of 2020. The rampant illegal mining activities further harm state finances, exacerbated by the absence of sophisticated infrastructure to monitor mining areas and potential sites in real time using satellite imagery. Additionally, inadequate distribution of corporate social responsibility (CSR) funds has left mining and affected areas without proper support, highlighting the urgent need for CSR regulations in the future be regulated at the legislative level. Furthermore, regulatory efforts to adopt green technology remain insufficient, with a lack of fiscal incentives and investment protection for companies committed to sustainable practices. The situation is further worsened by the lack of transparency in the mining sector, further exacerbates the situation as there is still no clear mechanism to ensure accountability or provide the public with access to crucial mining operation data. Based on the complex mining problems from multi-sectors, the regulatory reform framework must involve authorized government institutions and involve public participation in regulatory reform and the outcomes of the rules formed can accommodate the protection of public participation and protection of public rights in mining, respond to effective law enforcement and provide great contribution to the state, society, and global collaboration.